Karuk ecological fire management practices promote elk habitat in northern California. Issue 7 (25th May 2022) - Connor, Thomas; Tripp, Emilio; Tripp, Bill; Saxon, B. J.; Camarena, Jessica; Donahue, Asa; Sarna‐Wojcicki, Daniel; Macaulay, Luke; Bean, Tim; Hanbury‐Brown, Adam; Brashares, Justin
Abstract: After a century of fire suppression and accumulating fuel loads in North American forests, prescribed burns are increasingly used to prevent conditions leading to catastrophic megafire. There is widespread evidence that prescribed fire was used by Indigenous communities to manage natural and cultural resources for thousands of years. Wildlife habitat is an example of an ecological response that was actively managed with prescribed burns by Indigenous American peoples and is an important factor in western US forest management planning, restoration and climate resilience efforts. We analysed the effects of modern prescribed burns informed by traditional ecological knowledge (TEK) on the predicted change in elk winter habitat in Karuk aboriginal territory in Northern California between 2013 and 2018 using species distribution and simultaneous autoregressive modelling techniques. Burn types most closely resembling Karuk traditional practices, specifically those incorporating multiple‐year broadcast burns, had significant positive effects on elk winter habitat suitability. Conversely, concentrated burns focused solely on reducing fuel loads had significant negative effects on elk winter habitat suitability. However, areas where these fuel‐reduction burns were combined with multiple years of broadcast burns featured the highest increases in habitat. Synthesis and applications . Our results suggest that transitioning to prescribed burns that more closely follow Karuk traditional ecological knowledge will promote elk habitat in the region. This would be best achieved through continuing to work closely with Indigenous representatives to plan and implement cultural fire prescriptions on a landscape scale, a trend we posit would benefit environmental management efforts across the globe. Abstract : Our results suggest that transitioning to prescribed burns that more closely follow Karuk traditional ecological knowledge will promote elk habitat in the region. This would be best achieved through continuing to work closely with Indigenous representatives to plan and implement cultural fire prescriptions on a landscape scale, a trend we posit would benefit environmental management efforts across the globe.